Structural control and genesis of the Au-quartz veins from the Serra do Cavalo Magro orogenic gold deposit, southern Ribeira Belt, Brazil - Malta, Isaac Siles (2018)
The Serra do Cavalo Magro orogenic gold deposit is located in the southern Ribeira Belt, Brazil. Gold-quartz veins are hosted by Calymmian (1500-1450 Ma) metasedimentary and metabasic rocks and Ediacaran (610-600 Ma) granitic rocks. Petrological modeling indicates peak metamorphic conditions from 560°C and 7 kbar (chlorite-biotite phyllite) to 625°C and 6.8 kbar (garnet-biotite phyllite) recorded in immediate host rocks. Gold mineralization occurs in extensional and shear quartz veins structurally-controlled by NE-trending second-third order sinistral transcurrent shear zones. NNW-trending, vertical and subhorizontal extensional veins are oriented 55-85° in relation to the fault planes, indicating that the shear zones were severely misoriented for frictional react ivation. Deformation within the shear zones was accommodated by bulging recrystallization of quartz aggregates, while feldspar aggregates from granitic protoliths underwent cataclastic flow or were replaced by sericite-epidote producing phyllonites. Gold precipitated during stages of vein deformation within microfractures in my lonitized shear veins with quartz previously subjected to bulging recrystallization. Ore-fl uids are recorded in coexisting C02-N2, l-hO-NaCl-CaCh and H20-C02-N2-NaCI-CaCh fluid inclusions oflow to moderate salinities (1-18 w1.%NaCl eq.). Microthennometric data indicate entrapment conditions of240-260 °C and 0.4-2.5 kbar, recording hydrostatic to supralithostatic fluid pressure conditions. High-temperature l-hO-NaCl-CaCh-KCl brine inclusions (up to 475 DC, 25-33 wt.% aCl eq.) are considered unrelated with gold mineralization. Strong fluid pressure fluctuations from 0.4 to 1.6 kbar are associated with earthquake cycles and the faultvalve behavior. In this scenario, gold mineralization was associated with fluid immiscibility. There is evidence for restricted fluid mixing, but this process is interpreted as unrelated with gold mineralization. Available geochronological data and structural-petrological relationships with host rocks and shear zones indicate that mineralization was formed within 580-540 Ma in post-peak metamorphic episodes. The hydrothermal ore-fluids were likely produced by devolatilization reactions during prograde metamorphism at deeper levels. Subsequently, the metamorphic-hydrothermal fluids were channeled upwards within the strike-slip shear zones into rocks that have been metamorphosed and devolatilized at earlier times.